Ekonomi Hijau: Konsep, Prinsip, dan Relevansinya dalam Pembangunan Berkelanjutan - Fifi Yanti, Maria; Suwar, Arizul (Economia: Journal of Economics and Management, 2024)
This study aims to examine the concept of green economy, its underlying principles, and its relevance to sustainable development through a literature review approach. The method used is qualitative research, with data sources derived from scientific literature, including journal articles, academic books, and reports from international organizations. Data were collected through documentation techniques and analyzed using descriptive, comparative, and literature synthesis methods to obtain a comprehensive understanding. The findings indicate that the green economy is an approach that integrates economic growth with environmental sustainability and social equity. Although variations in definitions are found across the literature, there is a common core emphasizing resource efficiency, emission reduction, and economic inclusivity. These principles serve as the foundation for implementing green economy practices, such as renewable energy development, circular economy application, and the expansion of green investment. In the context of sustainable development, the green economy plays a significant role in promoting balance among economic, social, and environmental dimensions. However, the implementation of the green economy still faces several challenges, including high costs, market resistance, and disparities in capacity among countries. Therefore, strong policy support and collaboration between government and the private sector are essential to drive the transition toward a more sustainable economic system. Abstrak Penelitian ini bertujuan untuk mengkaji konsep ekonomi hijau, prinsip-prinsip yang mendasarinya, serta relevansinya dalam pembangunan berkelanjutan melalui pendekatan kajian pustaka. Metode yang digunakan adalah penelitian kualitatif dengan sumber data berupa literatur ilmiah, seperti artikel jurnal, buku akademik, dan laporan lembaga internasional. Data dikumpulkan melalui studi dokumentasi dan dianalisis menggunakan teknik deskriptif, komparatif, serta sintesis literatur untuk memperoleh pemahaman yang komprehensif. Hasil kajian menunjukkan bahwa ekonomi hijau merupakan pendekatan yang mengintegrasikan pertumbuhan ekonomi dengan keberlanjutan lingkungan dan keadilan sosial. Meskipun terdapat variasi definisi dalam literatur, terdapat kesamaan inti yang menekankan efisiensi sumber daya, pengurangan emisi, serta inklusivitas ekonomi. Prinsip-prinsip tersebut menjadi dasar dalam implementasi ekonomi hijau melalui berbagai bentuk, seperti pengembangan energi terbarukan, penerapan ekonomi sirkular, dan peningkatan investasi hijau. Dalam konteks pembangunan berkelanjutan, ekonomi hijau memiliki peran penting dalam mendorong keseimbangan antara aspek ekonomi, sosial, dan lingkungan. Namun demikian, implementasi ekonomi hijau masih menghadapi berbagai tantangan, termasuk keterbatasan biaya, resistensi pasar, serta ketimpangan kapasitas antarnegara. Oleh karena itu, diperlukan dukungan kebijakan yang kuat serta kolaborasi antara pemerintah dan sektor swasta untuk mendorong transformasi menuju ekonomi yang lebih berkelanjutan.